Psychological challenges posed by the threat of covid-19 of nursing staff at Teaching hospital Jaffna - Wijesinghe, M.D.; Madhusanka, I.D.H.M.S.; Kamalarupan, L.; Jeyakumar, S. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Health care workers have to play a major role in combating this COVID-19 disease. The health care workers faced many psychological challenges during the COVID-19 pandemic. Objective: To assess the psychological challenges posed by the threat of COVID-19 for nursing staff at Teaching Hospital Jaffna. Methodology: This study was a hospital based descriptive cross-sectional study. A simple random sampling method was used and 393 nurses were recruited for the study. A self-administered questionnaire was used to collect data and data was analyzed by SPSS version 25. Results: The age range of the participants is 25 and 59 years old. Sri Lankan Tamils (57.5%) and Sinhalese (40.2%) represent the majority of the population. Male: female ratio is 1:2. Near 95% of the participants worried as covid 19 infection is a great danger to health and they worried about covid 19 situation (92.1%). However, they stated (88.9%), they have confident enough to managing covid 19 situation. Most of the participants felt annoyed (44.6%) at work due to the anxiety of getting the infection. Nearly half the nurses stated (54.2%) that they felt sad when the few health care workers skipped from caring the COVID- 19 patients. More than half of (56.4%) them felt that their health condition is threatening while caring the patients with Covid -19. Many nurses stated (92.6%) that they avoided close contact with their family when they suspect they are infected. The worries encountered by the participants about their kids during the COVID pandemic were: disturbed education of children (64.6%), and smartphone addiction of them (69.2%). Conclusion: A significant number of nurses faced various psychological challenges when work is posed by the threat of COVID-19.
Keywords: Psychological challenges; Nursing students; COVID-19